The Effect of Self-Regulated Learning on Self-Control in Table Tennis Learning - Muhamad Arif Ghazali; Dian Budiana; Didin Budiman (Universitas Pendidikan Indonesia, 2022)
The lack of student self-regulation in learning requires educators to implement a self-regulated learning model to improve the student ability to control themselves, have high confidence, be responsible, and be more independent in learning table tennis, thus the students are motivated to achieve the learning goals. The purpose of this study was to determine whether the SRL model in table tennis learning could improve the student self-control. The research method used was an experimental research method employing the Post-test Only Control Group Design. The population of this study were 80 students of the PETE for Elementary School Study Program of a university. The sampling technique used was the simple random sampling, involving 40 people. The instrument used to measure self-control was adopted from Tangney (self-control scale). The data analysis technique used was independent sample t-test employing SPSS 24 software for windows. The results showed that the self-regulated learning model had a significant effect on self-control in table tennis learning for PETE for Elementary School Study Program students.